Comparative assessment of individual rare-earth oxides and high-entropy rare-earth oxides reinforcements on the structural, physical, and radiation transmission properties of Inconel 718 - Gul, Ali Oktay; Albayrak, M. Gokhan; Guler, Omer; Ozkul, Iskender; Baykal, Duygu Sen; Almisned, Ghada; Tekin, H. O. (Pergamon-Elsevier Science Ltd, 2026)
This study addresses a fundamental materials design question for radiation-resistant superalloys: whether rareearth (RE) oxides are more effective when incorporated individually or when introduced collectively in a highentropy rare-earth oxide (HE-RE2O3) form. In this context, Inconel 718 (IN718) composites were reinforced with single RE2O3 phases such as Sm2O3, Tm2O3, Er2O3, Yb2O3, Eu2O3, and La2O3 at 10 wt% and with a mechanically alloyed HE-RE2O3 phase at 1-20 wt%. Structural analyses confirmed the formation of a single-phase HE-RE2O3 with a cubic bixbyite structure and its stable integration into the IN718 matrix. Gamma-ray shielding properties were systematically evaluated over a wide photon energy range. The HE-RE2O3 reinforced samples, particularly at higher loadings, exhibited consistently higher mass and linear attenuation coefficients, elevated effective atomic numbers, reduced half-value layers, and lower buildup factors compared to both the base alloy and singleoxide reinforced counterparts, demonstrating a clear collective attenuation effect. Fast neutron removal cross sections showed more moderate variations, reflecting the dominance of neutron scattering and mass-dependent interaction mechanisms rather than atomic number effects. It can be concluded that incorporating RE elements through a high-entropy oxide configuration provides a more effective and collective compositional contribution for enhancing the radiation shielding performance of IN718 than adding RE oxides individually, offering a promising pathway for advanced nuclear and radiation-relevant applications.
Keywords: Inconel 718; High-entropy; Rare-earth oxides; Gamma-ray shielding; Fast neutron removal cross section; Radiation matter interaction